An Empyrean Forge: designing an in-orbit manufacturing system for starship production - Beckman, Jacob (My University, 2025)
Current manufacturing and space launches produce several challenges that must be remedied if space exploration is to continue to advance into the new age. By synthesizing a series of case studies and historical research, this paper has developed a system of operations and the beginnings of physical models of a process known as the Empyrean Forge (the “Forge”). By implementing a three-step chain, the Empyrean Forge strives to create a fully-automated, in-situ, spacecraft manufacturing protocol. The goal of this research is to provide the basis for this protocol by combining the harvesting of raw materials from celestial bodies, refining that material into feedstock, and then using that feedstock to print all components of a spacecraft equitable to or superior to the modern space shuttle. In doing so, financial, environmental, and manufacturing inefficiencies are resolved (or at least lessened), which would allow for faster and more effective development as the industry proceeds to enter Space 4.0.
Keywords: Additive manufacturing; In-situ manufacturing; 3D printing; Automated engineering; Aerospace engineering